POLITICAL AND CONSTITUTIONAL INSTABILITY IN BOLIVIA: HISTORY AND IMPACTS ON MERCOSUR MEMBERSHIP - Azevedo, Caio Cabral; Barbosa Filho, Ronaldo Thomaz Cordeiro (Seven Editora, 2025)
This article correlates the political and constitutional instability of Bolivia and its distant process of accession to MERCOSUR, highlighting the difficulties faced due to internal crises and constitutional reforms. The analysis includes the relationship between political transformations and regional integration, as well as exploring how government challenges have affected the negotiations and ratifications necessary for membership. The methodology adopted is logical-legal, with bibliographic and documentary analysis, addressing the main theoretical landmarks on the Bolivian political history and the process of joining MERCOSUR. The article concludes that Bolivia's accession to MERCOSUR reflects the country's effort to overcome its historical political and constitutional instability, being an opportunity to consolidate democratic institutes and strengthen regional integration and development.DOI: https://doi.org/10.56238/sevened2024.037-133